Dust-aggregate impact into granular matter: A systematic study of the influence of projectile velocity and size on crater formation and grain ejection - Planes, María Belén (2017)
Context. Dust impact into granular materials leads to crater formation and material ejection. Aims. The impact of dust aggregates, composed of a number Np of grains, into a granular bed consisting of the same grains is studied as a function of impact velocity v and projectile size Np. No gravitational effects are included. Methods. Granular-mechanics simulations are used to study the outcome of dust-aggregate impacts. The granular bed and the aggregates are composed of silica grains and have filling factor 0.36. Results. Both the crater volume and the ejection yield increase sublinearly with total impact energy. No crater rims are formed. Crater shapes change from hemispheric to elongated when increasing either projectile size or velocity. The crater walls are compacted by the impact within a zone of a size comparable to the crater radius. Ejecta are produced at the edges of the impact; only a small fraction of the ejecta stem from the projectile. The energy distribution of the ejecta follows at high energies a 1/E2 decay reminiscent of sputtering from atomic targets. The maximum of the distribution is shifted to higher energies for larger projectiles; this is caused by the increasing depth from which ejected grains originate. Conclusions. Due to the dissipative nature of intergranular collisions and the porosity of the target, crater morphology and ejecta yield deviate characteristically from impacts into atomic materials.